2000
DOI: 10.1002/1521-4052(200009)31:9<856::aid-mawe856>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of epitaxial Nb(110) films on a-plane sapphire substrates: An x-ray study

Abstract: We studied the oxidation of epitaxial Nb(110) films on a‐plane sapphire substrates at elevated temperatures with x‐ray scattering techniques. Comparing atmospheric versus dry oxidation, we observe a different behaviour resulting in the formation of chemically and structurally different oxides. Under atmospheric conditions we obtain an unlimited growth of an amorphous Nb2O5 layer, while dry oxidation at 340°C and 10−3 mbar results in the growth of a crystalline and passivating NbO(111) layer with a final thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Studies have reported that the oxidation temperature of Nb and NbS 2 is slightly lower than that of the lubricating phase WS 2 . 42,43 which is consistent with the TG data in Figure 12. Unlike in the pure WS 2 or WSN coatings, the Nb and its sulfides in the WSNb coatings are preferentially combined with oxygen to be oxidized; thus the oxidation of WS 2 lubricating phase is delayed.…”
Section: Coatings Nanoindentation and Friction Behavior Of The Worn S...supporting
confidence: 90%
“…Studies have reported that the oxidation temperature of Nb and NbS 2 is slightly lower than that of the lubricating phase WS 2 . 42,43 which is consistent with the TG data in Figure 12. Unlike in the pure WS 2 or WSN coatings, the Nb and its sulfides in the WSNb coatings are preferentially combined with oxygen to be oxidized; thus the oxidation of WS 2 lubricating phase is delayed.…”
Section: Coatings Nanoindentation and Friction Behavior Of The Worn S...supporting
confidence: 90%
“…A similar Nb layer was used as a capping layer to prevent atmospheric attack of the multilayer after growth. A study of epitaxial (110) Nb films on sapphire has found that a stable layer of Nb 2 O 5 about 20 Å thick is formed, which provides effective long-term passivation [11].…”
Section: Fabricationmentioning
confidence: 99%